Perancangan Sistem Dalam Pengolahan Data Buah Sawit Berbasis Website Dengan Metode Object- Oriented Analysis And Design (OOAD) Program Studi Teknik Informstika - Ghepri Haikal; Pahrizal Pahrizal; Yuza Reswan; Ujang Juhardi (Jurnal Media Infotama, 2025)
Palm oil plantations play a vital role in supporting the rural economy, including in Tanjung Harapan Village, Kaur Regency. The process of buying and selling palm fruit by middlemen (toke sawit) is still largely conducted manually—from recording buyer data and purchase transactions to generating daily and monthly reports. This manual system often leads to problems such as data inconsistency, document loss, delayed reporting, and miscalculation during transactions. Therefore, an information system is needed to assist in managing data digitally, efficiently, and accurately.This research aims to design and develop a web-based palm fruit data management information system using the Object-Oriented Analysis and Design (OOAD) approach. The OOAD method was chosen to simplify the process of system analysis and design through various diagrams, including Use Case Diagrams, Class Diagrams, and Sequence Diagrams. The system was developed using the PHP programming language, MySQL database, and the CodeIgniter 4 framework. Its main features include managing buyer (toke) data, recording purchase transactions, generating daily and monthly reports, and printing reports.The results of the study show that the developed system functions effectively in helping palm fruit buyers manage transaction data digitally. It reduces recording errors, speeds up reporting processes, and improves work efficiency. Additionally, the OOAD approach proves to be effective in producing a well-structured system design that can be easily maintained and expanded in the future.